2023
DOI: 10.1037/fam0001042
|View full text |Cite
|
Sign up to set email alerts
|

Randomized preventive intervention for families: Adolescents’ emotional insecurity and attachment to fathers.

Abstract: The family communication project was a randomized preventive intervention designed to support families by improving interparental conflict behavior and the parent-child relationship, with the ultimate goal of decreasing emotional insecurity in the interparental relationship. Evidence for programs that may benefit father-adolescent attachment and adolescents' emotional insecurity in the marital context is a gap in the literature. According to the fathering vulnerability hypothesis, father-child attachment secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We also found that when fathers’ level of baseline marital adjustment was higher, there was less decline in dyadic conflict resolution between the posttest and 12-month assessment, a difference that was not found in the control conditions or with respect to mothers’ baseline marital adjustment. When considered together with previous published findings from the FCP sample that showed differentially positive gains in father–adolescent relationship outcomes after the intervention (Bergman et al, 2018; Cummings & Schatz, 2012; Hoegler et al, in press), the present findings may be indicative of a greater need to support fathers’ awareness of different ways to handle family conflict, especially when they are not feeling satisfied in their marriage and may be more vulnerable to the negative effects of marital conflict (Cummings, Merrilees, et al, 2010). Thus, future family-level interventions may benefit from the inclusion of content modules that are customized for each family member.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We also found that when fathers’ level of baseline marital adjustment was higher, there was less decline in dyadic conflict resolution between the posttest and 12-month assessment, a difference that was not found in the control conditions or with respect to mothers’ baseline marital adjustment. When considered together with previous published findings from the FCP sample that showed differentially positive gains in father–adolescent relationship outcomes after the intervention (Bergman et al, 2018; Cummings & Schatz, 2012; Hoegler et al, in press), the present findings may be indicative of a greater need to support fathers’ awareness of different ways to handle family conflict, especially when they are not feeling satisfied in their marriage and may be more vulnerable to the negative effects of marital conflict (Cummings, Merrilees, et al, 2010). Thus, future family-level interventions may benefit from the inclusion of content modules that are customized for each family member.…”
Section: Discussionsupporting
confidence: 67%
“…For example, mothers, fathers, and their adolescent children all showed statistically significant pretest to posttest increases in knowledge about how to handle family conflicts more constructively, and fathers in the treatment groups reported that their adolescents were more emotionally secure about both interparental and parent–adolescent relationships (Cummings & Schatz, 2012). Further, when adolescents participated in the intervention sessions with their parents, they reported significantly more secure attachment to their fathers and mothers at posttest (Cummings & Schatz, 2012; Hoegler et al, in press).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the small mean-level differences in favor of security with mothers, more efforts are recommended to include fathers in interventions aimed at promoting secure attachment and positive family relationship. Recently, Hoegler et al (2023) showed that a family-based program aimed at improving the parent-child and marital relationship increased attachment security of adolescents with mothers and fathers.…”
Section: Discussionmentioning
confidence: 99%